Characterization of Organic Matter of the Laptev Sea Eroded Coastal Sediments: A Case Study from the Cape Muostakh, Bykovsky Peninsula; Geosciences; Vol. 11, iss. 2 - Grinko A. A. Andrey Alekseevich; Goncharov I. V. Ivan Vasilyevich; Oblasov N. V. Nikolay Vladimirovich; Gershelis E. V. Elena Vladimirovna; Shaldybin M. V. Mikhail Viktorovich; Shakhova N. E. Nataljya Evgenjevna; Zarubin A. G. Aleksey Gennadievich; Ruban A. S. Aleksey Sergeevich; Dubaev O. V. Oleg Viktorovich; Veklich M. A. Maksim Aleksandrovich; Mazurov A. K. Aleksey Karpovich; Semiletov I. P. Igor Petrovich (2021, 2021)
Title screen